2020
DOI: 10.1002/cnr2.1331
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival in patients with metastatic renal cell carcinoma in Russia, Kazakhstan, and Belarus: a report from the RENSUR3 registry

Abstract: Background Real‐world data describing outcomes of treatment among metastatic renal cell carcinoma (mRCC) patients are limited and heterogeneous. Aim RENSUR3 registry study assessed real‐world data on the use of therapies in mRCC and overall survival (OS) in Russia, Kazakhstan, and Belarus. Methods Patients were included in the retrospective multicenter registry study. To be eligible, patients were required to have mRCC diagnosed from January 2015 to January 2016. Anonymized data were collected through an onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
2
4
0
1
Order By: Relevance
“…In recent decades, multiple scholars have reported that lymph node invasion is a significant risk factor for survival in patients with MRCC. 5 , 21 In the present study, the roles of lymph node status in our constructed nomograms were consistent with those in previous reports, and the multivariable Cox regression model showed that N stage was inversely related to patient prognosis. Currently, there are limited reports regarding the specific number and location of metastatic sites in patients with MRCC.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In recent decades, multiple scholars have reported that lymph node invasion is a significant risk factor for survival in patients with MRCC. 5 , 21 In the present study, the roles of lymph node status in our constructed nomograms were consistent with those in previous reports, and the multivariable Cox regression model showed that N stage was inversely related to patient prognosis. Currently, there are limited reports regarding the specific number and location of metastatic sites in patients with MRCC.…”
Section: Discussionsupporting
confidence: 91%
“… 18 In addition, among patients with MRCC, those with clear cell carcinoma had a better prognosis than patients with non-clear cell carcinoma (31 vs. 24 months) in the multicenter Korean registry. 5 Similar to our result, patients with clear cell carcinoma exhibited a better prognosis than patients with non-clear cell carcinoma tissue types. Moreover, compared with clear cell carcinoma, collecting duct carcinoma and sarcomatoid dedifferentiation tissue types were significantly related to a worse prognosis according to our constructed nomogram.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations